Outside Front Cover: Plasma Process. Polym. 7/2022. Issue 7 (4th July 2022) - Hegemann, Dirk; Hanselmann, Barbara; Zuber, Flavia; Pan, Fei; Gaiser, Sandra; Rupper, Patrick; Maniura‐Weber, Katharina; Ruffieux, Kurt; Ren, Qun
Abstract : Outside Front Cover : Antibacterial activity based on the generation of reactive oxygen species (ROS) has been investigated. A doped metal oxide catalyst deposited by sputtering was postoxidized and covered by a hydrophobic plasma polymer film, allowing diffusion of water and ROS. Rapid bacterial inhibition was observed even during storage in the dark, which can be reactivated by light exposure. The developed multifunctional coating can be deposited on various materials including polymers such as catheters or nonwovens. Further details can be found in the article by Dirk Hegemann, Barbara Hanselmann, Flavia Zuber, Fei Pan, Sandra Gaiser, Patrick Rupper, Katharina Maniura‐Weber, Kurt Ruffixseux, and Qun Ren (e2100246 )